Survey of the Heteroptera (Hemiptera) on pastures from Espírito Santo state, Brazil: new records, range extension, and notes of potential pests - Vélez, Mayra; Coelho, Lívia Aguiar; Martins, David dos Santos; Ferreira, Paulo Sergio Fiuza (EntomoBrasilis, 2020)
Espírito Santo is a Brazilian state that has a wide variety of habitats, providing a high biological diversity of fauna and flora. However, few reports had been shown about the insect diversity of this region, especially of heteropterans insects that inhabit on pasture ecosystems. In the present study, forty-three species of Heteroptera belonging to thirteen families were collected on pastures on Espírito Santo state, Brazil: Alydidae (1 sp.), Berytidae (3 sp.), Blissidae (1 sp.), Coreidae (7 sp.), Miridae (16 sp.), Nabidae (1sp.), Pentatomidae (3 sp.), Pyrrhocoridae (1 sp.), Reduviidae (6 sp.), Rhopalidae (1 sp.), Rhyparochromidae (1sp.), Thaumastocoridae (1 sp.) and Tingidae (1 sp). Among the species; Cebrenis tenebrosa (Brailovsky, 1995) is recorded for the first time in Brazil. The range extension is also included for several heteropterans collected on the Espírito Santo state. The following species: Blissus aff. antillus (Leonard, 1968); Collaria oleosa (Distant, 1883); Oebalus ypsilongriseus (De Geer, 1773), and Trigonotylus tenuis (Reuter, 1893) were observed causing damages on pastures, therefore, in this study, we suggested those species as potential pastures pests. This study aims to increase the knowledge about the heteropterans and to show the presence of some pest species that may cause serious damage to pastures and consequently affect the economy of cattle breeders on the state.